Visual control of obstacle avoidance during locomotion: Strategies in young children, young and older adults - Patla, Aftab E.; Prentice, Stephen D.; Gobbi, Lilian T. (Elsevier, 1996)
The focus of this chapter is on understanding how obstacle avoidance during locomotion is affected by normal aging process and how this adaptability in locomotor system develops as children acquire independent bipedal locomotion. Obstacle avoidance paradigms offer a rich source of material for understanding the unique sensorimotor integration common to many visually guided movements. Based on studies on young healthy adults, we have proposed a jigsaw puzzle metaphor summarizing the key ingredients for successful obstacle avoidance. The nature of visual and kinesthetic input and the contribution of the effector system properties form the pieces of the puzzle. Studies on healthy older adults reveal relatively well preserved obstacle avoidance strategies, although there are some differences when compared to the healthy young adults. Deterioration in sensory input and effector system characteristics shows up as adaptive changes in feedforward control of limb trajectory over obstacles. This suggests that the puzzle, is relatively robust with cracks appearing in some pieces. Preliminary studies on children provide interesting signposts for the development of stable obstacle avoidance strategies. High failure rate and poorer control of limb trajectory over obstacles characterize the gait patterns of young children in a cluttered environment. This suggests that the pieces of the puzzle have to be sculpted and merged into a coherent picture during the development process. © 1996 Elsevier B.V. All rights reserved.
Keywords: aging; development; intersegmental dynamics; locomotion; Obstacle avoidance